Fuel-saving kiln for fish - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Engineers and technologists from the Natural Resources Institute (NRI) have produced a kiln for fish-smoking that uses only 25- 35% of the woodfuel that traditional models require. Nile perch is now the ma or commercial species in Lake Victoria,...